Marketability study of second generation cordless telephone or Smartfon in Klang Valley / Shuib Bakar - Bakar, Shuib (1993)
This is a marketability study of 2nd generation cordless telephone or Smartfon in Klang Valley. The selection of the area as regional segmentation due to its expected potential demand for the service.